2013
DOI: 10.1007/s10936-013-9241-y
|View full text |Cite
|
Sign up to set email alerts
|

Context Improves Comprehension of Fronted Objects

Abstract: Object-initial clauses (OCs) are associated with more processing difficulties than subject-initial clauses (SCs) in a number of languages (e.g. English, German and Finnish), but a supportive context can reduce or neutralize the difference between SCs and OCs with respect to reading times. Still, it is unresolved how context can affect the comprehension of OCs. In the present self-paced reading study of Danish, we therefore investigated both reading times, comprehension accuracy and response times for OCs and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…As expected, Kristensen et al (2013) found greater overall processing difficulties for OS sentences: Responses to comprehension questions were slower for OS sentences than for SO sentences, and responses were more frequently incorrect. However, the study also showed a significant improvement of comprehension when OS sentences occurred in supportive discourse context.…”
Section: Figure 2 Response Accuracy and Response Time From Reading Ssupporting
confidence: 76%
See 4 more Smart Citations
“…As expected, Kristensen et al (2013) found greater overall processing difficulties for OS sentences: Responses to comprehension questions were slower for OS sentences than for SO sentences, and responses were more frequently incorrect. However, the study also showed a significant improvement of comprehension when OS sentences occurred in supportive discourse context.…”
Section: Figure 2 Response Accuracy and Response Time From Reading Ssupporting
confidence: 76%
“…The effect of context on syntactic processing is seen in two recent studies of sentence processing in Danish (Kristensen, Engberg-Pedersen, & Poulsen, 2013;Kristensen, et al, in review). Danish is well-suited for examining word order processing, as both objects and subjects can occur in the first position of Danish clauses.…”
Section: Two Experiments On the Effect Of Discourse Context On Syntacmentioning
confidence: 99%
See 3 more Smart Citations